To what Extent Does Globalization Influence Climate Change Sensitivity in Sub-Saharan Africa Countries: Evidence from DCCE-MG Approach - Aghazadeh, Sahar; Odugbesan, Jamiu Adetola; Saei, Aliakbar (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Though, the issue of climate change is a global challenge that has attracted the attention of various stakeholders, but the understanding of various contributing factors to address the challenge still remains a moot topic. Thus, this study investigates the sensitivity of climate change in Sub-Saharan Africa (SSA) countries to overall globalization, dejure and defacto globalization, population, urbanization and economic growth using a panel data covering the period from 1990-2018. The estimations were performed using the novel Westerlund and Erdgerton panel cointegration approach to estimate the co-movement of the variables in the long run, while the long-run relationship was estimated using the “Dynamic Common Correlated Effect-Mean Group” (DCCE-MG) techniques and used the “Dynamic OLS” and “Fully Modified OLS” for robustness check. Empirical findings reveal the long-run relationship between the variables of interest. In addition, our study shows a significant and positive influence of overall globalization, dejure and defacto globalization, economic growth and urbanization on climate change in SSA countries in the long-run, while population was found to have a negative and significant long-run relationship with climate change. Finally, the findings implications and suggestions for policy makers in SSA countries were presented.